(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article presents an analysis of the developmental potential of an extended day group as a form of the educational process in the primary school. The author emphasizes the key role of the game in the work of an elongated day group. She substantiates its role in the development of creative competence, critical thinking, communicative skills.